2021
DOI: 10.1101/2021.05.20.444918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and dynamics of RNA guanine quadruplexes in SARS-CoV-2 genome. Original strategies against emerging viruses

Abstract: Guanine quadruplexes (G4) structures in viral genome have a key role in modulating viruses' biological activity. While several DNA G4 structures have been experimentally resolved, RNA G4s are definitely less explored. We report the first calculated G4 structure of the RG-1 RNA sequence of SARS-CoV-2 genome, obtained by using a multiscale approach combining quantum and classical molecular modelling and corroborated by the excellent agreement between the corresponding calculated and experimental circular dichroi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…reported the first calculated RNA G4 structure of RG‐1 and proved the stability of the RG‐1 G4 arrangement as well as its interaction with G4 ligands, such as PDP and CX‐3543. [ 53 ] Berberine is a potential anti‐SARS‐CoV‐2 drug and Oliva et al . investigated the binding properties of RG‐1 to Berberine compared to telomeric G4, [ 54 ] contributing to the development of G4 ligands that can discriminate between binding to DNA and RNA G4s.…”
Section: Identification Of G4s In Sars‐cov‐2 Genomementioning
confidence: 99%
See 1 more Smart Citation
“…reported the first calculated RNA G4 structure of RG‐1 and proved the stability of the RG‐1 G4 arrangement as well as its interaction with G4 ligands, such as PDP and CX‐3543. [ 53 ] Berberine is a potential anti‐SARS‐CoV‐2 drug and Oliva et al . investigated the binding properties of RG‐1 to Berberine compared to telomeric G4, [ 54 ] contributing to the development of G4 ligands that can discriminate between binding to DNA and RNA G4s.…”
Section: Identification Of G4s In Sars‐cov‐2 Genomementioning
confidence: 99%
“…[ 27 ] However, due to the bioavailability issues, it was withdrawn from further trials. Recent research showed that CX‐3543 can potentially be seen as an effective compound to stabilize SARS‐CoV‐2 RG1, [ 53 ] indicating the potential of CX‐3543 for COVID‐19 therapy. Ribavirin is a well‐known antiviral drugs used for treating COVID‐19.…”
Section: G4 Ligands Against Sars‐cov‐2mentioning
confidence: 99%